Reversal of lipopolysaccharide-induced cardiomyocyte apoptosis via α7nAChR by dexmedetomidine: Dexmedetomidine affects cardiomyocyte apoptosis via α7nAChR - Feng, Mingjing; Zheng, Changlu; Li, Xiangyun; Chen, Baozeng; Li, Weiwei (Cellular and Molecular Biology, 2024)
This study aims to analyze the reversal of lipopolysaccharide (LPS)-induced cardiomyocyte apoptosis via α7nAChR by dexmedetomidine (Dex), so as to provide references for clinical treatment of myocardial disorders in the future. First, the research team divided cardiomyocytes (H9C2) were divided into a control group (normal culture), an LPS group (LPS-induced injury model), and an experimental group (pretreated with Dex before LPS induction). Subsequently, lactate dehydrogenase (LDH) and cell activity were detected, and the research team found that the LDH content of the control, experimental and LPS groups were in ascending order (P<0.05). The cell viability decreased and apoptosis increased in the LPS group, with cells mainly concentrating in the G2-M phase; the viability increased and apoptosis decreased in the experimental group, with blocked G1-G0 phase (P<0.05). This demonstrates that Dex can reverse LPS-induced apoptosis in cardiomyocytes. Subsequently, the research group also detected the expression of α7nAChR and NF-κB/AKT pathway, and it was seen that the expression of α7nAChR in the LPS group was higher than that in the control group, with activated NF-κB/AKT pathway; the α7nAChR expression in the experimental group was further elevated, but the NF-κB/AKT pathway was inhibited (P<0.05). The effects of Dex on cardiomyocytes were seen to be related to the α7nAChR and NF-κB/AKT pathways.